Zoom vs. Microsoft Teams: Students’ Preference - Patria Handung Jaya; Yulisti Septiani (Ahmad Dahlan Journal of English Studies, 2023)
Learning is a process from knowing nothing to knowing more and it can be done by ourselves or teachers. However, normally learning with a teacher is done face-to-face, but due to the pandemic, much of the learning was changed to online. Online learning is done virtually, usually using media as a learning platform; the media used for online learning is Zoom and Microsoft Teams. This article aims to discover Student's Preference Between Zoom and Microsoft Teams as The Media for Online Learning and their reasons for choosing the media. In addition, this research was conducted using a quantitative method; the researchers distributed a Google form to students, which contained several questions they had to answer related to the Zoom platform and Microsoft Teams as a medium for online learning. They also had to tell the reasons they chose the media. The result of this research is divided into two categories: completeness of features and convenience of use. Zoom and Microsoft Teams have some of the same features and also have their advantages and disadvantage. Most students choose Microsoft Teams because of the complete features, but they mostly choose Zoom for convenience. From the results obtained, it is hoped that in the future, people who read this paper will find it easier to choose what platforms they will use for online learning and choose the right media. It is hoped that it can increase the enthusiasm of students to learn.